Annesinin vefatından dolayı Haydar Bammat'a gönderilmiş başşağlığı mektubu - (:unkn) unknown (My University, 1931)
Başsağlığı mektubudur.
Keywords: Bammat, Haydar, 1890-1965; Bammat, Reşide, 1866-1931; Condolence letters; Paris-France